OFR-27-80 Polychlorinated Biphenyls: Regulations And Substitutes A Compliance Manual For The U. S. Mining Industry - Robert A. Westin (The National Institute for Occupational Safety and Health (NIOSH), 1979)
Polychlorinated Biphenyls (PCBs) have been widely used as fire resistant dielectri coolants in electrical equipment used in mining applications, including transformers capacitors, electric motors, and electromagnets. In addition, PCBs have been used in hydraulic fluids and heat transfer fluids, and are present in many oil filled transformers. The Environmental Protection Agency recently banned the manufacture of PCBs and equipment using PCBs, and imposed strict requirements on the continued use and disposal of existing PCB equipment. This manual discusses the EPA requirements, suggest ways to decrease the risks resulting from continued use of PCB equipment, and surveys the non-PCB equipment that is available as replacements for the PCB electrical equipment presently used in mines.